Inside Back Cover: Ultrafast Damage Following Radiation‐Induced Oxidation of Uracil in Aqueous Solution (Angew. Chem. Int. Ed. 11/2013). Issue 11 (4th March 2013) - López‐Tarifa, Pablo; Gaigeot, Marie‐Pierre; Vuilleumier, Rodolphe; Tavernelli, Ivano; Alcamí, Manuel; Martín, Fernando; Hervé du Penhoat, Marie‐Anne; Politis, Marie‐Françoise
<x xml:space="preserve">Abstract</x> Of primary cosmic rays, about 99% are nuclei of the most abundant atoms (H, He, Fe). These ions induce multiple ionization events in biomaterials that lead to the Coulombic explosion of biomolecules. In their Communication on page 3160 ff., M.‐A. Hervé du Penhoat, M.‐F. Politis, et al. use first‐principle molecular dynamics to examine the hydroxylation of uracil by an ionized water molecule. The film shows snapshots taken along the picosecond timescale of this reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>